STUDENTS LEARNING STYLE BY USING NEIL FLEMING’S VARK MODEL AND INVENTORY - Jumrah; Muhammad Arif Paturusi; Maharida (FKIP Unismuh Makassar, 2022)
This research deals language learning styles of the first-grade students of SMP Neheri 3 Bontomarannnu. The problem statement are : (1) Which language learning style is the most dominant used by the first grade students of SMP Negeri 3 Bontomarannu? (2) Do the students’ learning styles influence their English achievement? The objective of the research is to find out the most dominant language learning style used by the first-grade students of SMP Negeri 3 Bonromarannu. (2) To found the influence of studens leaning style toward their achievement in learning English at SMP Negeri 3 Bontomarannu. The type of the research is descriptive quantitative. The research samples were 26 students. Then they were classified into four categories of learning style through learning style test: visual, auditory, read/write and kinesthetic learning style. In collecting the data, the researcher used a questionnaire and students’ score achievement.